PERKEMBANGAN MOTORIK ANAK USIA 5 â 6 TAHUN DI TK ISLAM SELARAS JAKARTA TIMUR - Novitawati, Novitawati (Tarbiyah, 2014)
Physical development is considered as one of the important things to learn, since it can directly or indirectly affect children behaviors in their daily life. Thus, therefore this research is conducted and is aimed at knowing motoric development of children in age between 5-6 years old at Islamic Kindergarten (TK Islam) Selaras, Jakarta Timur. This is a descriptive qualitative research and using observation instrument which is developed based on the act of the Ministry of National Education, Number 58 Year 2009, about the Standard of Young Learners Education, specifically the motoric development of children age 5-6 years old. The study showed that the motoric development of children age 5-6 years old at the TK Islam Selaras, Jakarta Timur is relatively evolved as expected, this is based on the data that 5 of 6 children are developed very well in their rough motoric, and only a kid is developed as expected. While the smooth motoric development, it is found out that 3 kids are developed very well, while 3 others are developed as expected. The study also recommends the school to increase more the program which stimulates smooth motoric development of children, as well as providing opportunities for children to develop their smooth motoric skills, especially in terms of drawing, drawing round environment, and cutting patterns. Parents are also expected to provide more opportunities for children to explore a variety of activities to stimulate childrens motoric development, especially smooth Â motoric development, as well as providing guidance to the children in drawing, cutting out the pattern, and buttoning clothes at home.Â Keywords: motoric development, rough motoric, smooth motoric, TK Islam Selaras